An examination of the cryptocurrency pump-and-dump ecosystem. Issue 4 (July 2021) - Hamrick, J.T.; Rouhi, Farhang; Mukherjee, Arghya; Feder, Amir; Gandal, Neil; Moore, Tyler; Vasek, Marie
Abstract: The recent introduction of thousands of cryptocurrencies in an unregulated environment has created many opportunities for unscrupulous traders to profit from price manipulation. We quantify the scope of one widespread tactic, the "pump and dump", in which actors coordinate to bid up the price of coins before selling at a profit. We joined all relevant channels on two popular group-messaging platforms, Telegram and Discord, and identified thousands of different pumps targeting hundreds of coins. We find that pumps are modestly successful in driving short-term price rises, but that this effect has diminished over time. We also find that the most successful pumps are those that are most transparent about their intentions. Combined with evidence of concentration among a small number of channels, we conclude that regulators have an opportunity to effectively crack down on this illicit activity that threatens broader adoption of blockchain technologies. Highlights: We gather the most comprehensive dataset on cryptocurrency pump and dump schemes. Pumped coins experience a modest price increase, but it is higher for less popular coins. Brazen pumps are more "successful" than those obscuring their corrupt intent. High concentration among pump channels creates opportunity for regulators.